Effect of galvanic vestibular stimulation on axial symptoms in Parkinson's disease. (10th February 2022) - Kataoka, Hiroshi; Okada, Yohei; Kiriyama, Takao; Kita, Yorihiro; Nakamura, Junji; Shomoto, Koji; Sugie, Kazuma
Postural imbalance, abnormal axial posture, and axial rigidity are the characteristic features of Parkinson's disease (PD), and they are referred to as axial symptoms. The symptoms are difficult to manage since they are often resistant to both L-DOPA and deep brain stimulation. Hence, other treatments that can improve Parkinsonian axial symptoms without adverse effects are required. Vestibular dysfunction occurs in PD since neuropathological changes and reflex abnormalities are involved in the vestibular nucleus complex. Galvanic vestibular stimulation (GVS), which activates the vestibular system, is a noninvasive method. This review aimed to assess the clinical effect of GVS on axial symptoms in PD. To date, studies on the effects of GVS on postural instability, anterior bending posture, lateral bending posture, and trunk rigidity and akinesia in PD had yielded interesting data, and none of the patients presented with severe adverse events, and the others had mild reactions. GVS indicated a possible novel therapy. However, most included a small number of patients, and the sample sizes were not similar in some studies that included controls. In addition, there was only one randomized controlled clinical trial, and it did not perform an objective evaluation of axial symptoms. In this type of research, vestibular contributions to balance should be distinguished from others such as proprioceptive inputs or nonmotor symptoms of PD.